2016
DOI: 10.1002/j.0022-0337.2016.80.12.tb06236.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Attendance Be Required in Lecture Classrooms in Dental Education? Two Viewpoints

Abstract: This Point/Counterpoint discusses the long-argued debate over whether lecture attendance in dental school at the predoctoral level should be required. Current educational practice relies heavily on the delivery of content in a traditional lecture style. Viewpoint 1 asserts that attendance should be required for many reasons, including the positive impact that direct contact of students with faculty members and with each other has on learning outcomes. In lectures, students can more easily focus on subject matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Lecture absenteeism is a controversial debate with regard to its connection to academic performance. Numerous studies have reported on the causal relationship between non-attendance and academic achievement [1,5]. Looking at the current data, several factors had an impact on students' attitude towards classroom attendance.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Lecture absenteeism is a controversial debate with regard to its connection to academic performance. Numerous studies have reported on the causal relationship between non-attendance and academic achievement [1,5]. Looking at the current data, several factors had an impact on students' attitude towards classroom attendance.…”
Section: Discussionmentioning
confidence: 67%
“…However, students' attendance in classrooms had declined significantly in the recent years on a local and national levels [4]. This maybe attributed in part to change in attitude, their ability to learn the material on their own and today's era of evolving online education rendering class attendance unneeded [5]. Other factors linked to students' interest in attending classroom lectures include class subject (the scope and difficulty of the subject), faculty member lecturing style and transportation to school, stress, time management and poor health were also reported as secondary factors contributing to classroom attendance [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, to reduce additional variables that would likely affect attendance, we purposely avoided adding digital media forms of instruction (e.g., video recordings of lectures). Currently, however, when online and digital media are both desired and may enhance performance in dental education, 1 there will be a need for further study of how to best use these modalities in light of their potential effect on attendance 20 , 21 . Our study indicates a need for further research to determine which form or blend of instructional modalities (live lecture, recordings/online resources) will optimize student performance in OP.…”
Section: Discussionmentioning
confidence: 89%
“…Improving student performance on examinations and course grades is one measure of effective teaching and learning. Among the many student‐and instructor‐driven variables that can contribute to improved performance, one that is increasingly scrutinized in this era of digital and online education is lecture attendance 1 . There is a growing trend among students in higher education to not attend lectures 2 .…”
mentioning
confidence: 99%